Investigation of the flux dynamics in KCa2Fe4As4F2 single crystal by ac susceptibility measurements. (1st May 2022) - Gao, Li-Xin; Wang, Teng; Xiao, Qi-Ling; Lu, Wen-Lai; Chen, Fei; Mu, Gang; Ge, Jun-Yi
Abstract: Systematic ac susceptibility measurements have been performed to study the flux dynamics in a high quality KCa2 Fe4 As4 F2 single crystal. The irreversible line in the vortex diagram is closed to the H c 2 ( T ) line suggesting the strong intrinsic pinning in this material. The critical field H c r = 0.4 T between single vortex pinning state and collective pinning state is obtained according to thermally activated flux creep model. The abnormal behavior in the single vortex pinning region that the activation energy U follows a ∼ H − 0.53 dependence might arise from the planar defects of submicron scale. The strong field dependences of the activation energy in both regions suggest that artificial pinning centers are needed to enhance the pinning for practical applications. Moreover, the field and current density dependences of the activation energy at relatively high fields are determined as U ( J, H d c ) ∝ J − 0.26 H − 1.2 .